2023
DOI: 10.3390/ijerph20032015
|View full text |Cite
|
Sign up to set email alerts
|

Age and Maturation Matter in Youth Elite Soccer, but Depending on Competitive Level and Gender

Abstract: This study aimed to explore the relevance of the relative age effect (RAE), maturity status and anthropometry, and their influence on coaches’ assessment of players’ performance, analyzing both genders and different types of academies (elite vs. non-elite). The sample included 603 soccer players (385 male), from the under 12 (U12), under 14 (U14) and under 16 (U16) categories, belonging to elite and nonelite teams. Coaches’ assessment of players´ performance, chronological age, anthropometric characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Frontiers in Physiology frontiersin.org 2023; Pezoa-Fuentes et al, 2023), sports (Müller et al, 2017;Gryko, 2021) and especially in young soccer players (Asadi et al, 2018;Müller et al, 2018;Peña-González et al, 2022;Ginés et al, 2023). These evidences found in this study may be important for coaches, technicians, physicians, physiotherapists, and directors of youth soccer academies, as the analysis of BC and PF should be analyzed by MS and not by CA.…”
Section: Figurementioning
confidence: 56%
“…Frontiers in Physiology frontiersin.org 2023; Pezoa-Fuentes et al, 2023), sports (Müller et al, 2017;Gryko, 2021) and especially in young soccer players (Asadi et al, 2018;Müller et al, 2018;Peña-González et al, 2022;Ginés et al, 2023). These evidences found in this study may be important for coaches, technicians, physicians, physiotherapists, and directors of youth soccer academies, as the analysis of BC and PF should be analyzed by MS and not by CA.…”
Section: Figurementioning
confidence: 56%
“…Indeed, a recent study conducted on Spanish youth soccer demonstrated how RAEs are not associated with players’ likelihood of accessing the next developmental stage [ 70 ]. Moreover, Ginés et al [ 71 ] also showed how, in Spanish male academy soccer, coaches’ selections are not influenced by chronological age, with research conducted by Hill et al [ 26 ] revealing it was not a significant predictor of perceived performance when compared to the biological maturation effect. In line with this, Part 2 of this study highlighted players’ ability to develop into Level 1 players once a senior was not influenced by their relative age, thus indicating early born overrepresentation at the senior level may only be attributed to the knock-on effect (i.e., players selected from a pool of players already affected by RAEs) [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study did not find RAE in both male and female senior elite beach handball athletes and failed to establish an association with competitive success as determined by the final position achieved in world championships (Savassi et al, 2020). On the other hand, the study developed by Ginés et al (2023) that, although age and maturation are important in elite youth soccer, there are other important factors that are related to the competitive level and gender of the athletes.…”
Section: Introductionmentioning
confidence: 97%